Oxford reading tree : level 1+ : more songbirds phonics : cat naps - Donaldson, Julia ([S.l.] : Oxford University Press, 2012)
Written by award-winning author Julia Donaldson, Songbirds Phonics are highly decodable, beautifully illustrated real stories. In Cat Naps, Top Cat is feeling sleepy. The Level 1+ More Songbirds books consolidate phonics introduced to beginner readers in Songbirds Levels 1+, matching a sound to one letter: for example, 'o' as in 'dog.' The invaluable inside cover notes enable parents/carers and teaching assistants to support children's word recognition and comprehension. Also available: * More Songbirds Level 1+ Pack of 6 * More Songbirds Level 1+ Class Pack of 36 * Level 1+-2 eSongbirds Phonics CD-ROM, featuring e-versions of much-loved Songbirds stories for your interactive whiteboard, with audio activities and animations for consolidation and reinforcement.